2014
DOI: 10.2106/jbjs.m.00009
|View full text |Cite
|
Sign up to set email alerts
|

Augmentation of Tendon-to-Bone Healing

Abstract: Tendon-to-bone healing is vital to the ultimate success of the various surgical procedures performed to repair injured tendons. Achieving tendon-to-bone healing that is functionally and biologically similar to native anatomy can be challenging because of the limited regeneration capacity of the tendon-bone interface. Orthopaedic basic-science research strategies aiming to augment tendon-to-bone healing include the use of osteoinductive growth factors, platelet-rich plasma, gene therapy, enveloping the grafts w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
122
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(128 citation statements)
references
References 79 publications
6
122
0
Order By: Relevance
“…Nonetheless, numerous complications and adverse effects have been reported in clinical setting (e.g. intra-operative fracture, intra-articular complications, extra-articular abscesses) [348], clearly indicating that further research is necessary to elucidate the underlying mechanisms of tendon-to-bone healing and to translate safe and therapeutic interventions [349].…”
Section: Sutures and Screwsmentioning
confidence: 99%
“…Nonetheless, numerous complications and adverse effects have been reported in clinical setting (e.g. intra-operative fracture, intra-articular complications, extra-articular abscesses) [348], clearly indicating that further research is necessary to elucidate the underlying mechanisms of tendon-to-bone healing and to translate safe and therapeutic interventions [349].…”
Section: Sutures and Screwsmentioning
confidence: 99%
“…Other studies have looked at coating sutures with arginine-glycine-aspartic acid 10 (RGD) peptides to enhance cellular proliferation or collagen-coated sutures to support tendon-to-bone adhesion. 9,25 bFGF Fibroblastic growth factors, such as bFGF play an important role in tendon healing. The exogenous application of this agent through coated suture may accelerate the structural reorganization of tendon and thereby shorten the healing process.…”
Section: Biological Coating For Improvement Of Tissue Healingmentioning
confidence: 99%
“…It was reported that daily LIPUS treatment for 20 min enhanced bone adhesion and shortened the recovery time of fresh fractures, and it is being established as a treatment method in the field of orthopedics 4) . Recent animal studies have also shown that LIPUS accelerates tendon-bone healing 5) . We have reported the effect of LIPUS on bone formation around dental implants inserted into rabbit femur.…”
Section: Introductionmentioning
confidence: 99%